2020
DOI: 10.17691/stm2020.12.5.04
|View full text |Cite
|
Sign up to set email alerts
|

Periostin as a Biomarker of Allergic Inflammation in Atopic Bronchial Asthma and Allergic Rhinitis (a Pilot Study)

Abstract: The involvement of periostin in Th2-dependent allergic inflammation has been documented. However, the significance of periostin as a biomarker of local allergic inflammation in the nasal mucosa (NM) of patients with atopic bronchial asthma (BA) and allergic rhinitis (AR) is yet to be determined. The aim of the study was to determine the presence of periostin and evaluate its role as a non-invasive marker of allergic inflammation in the nasal secretions of children with atopic BA and AR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…In 2011, it was first reported that the serum periostin level could be utilized to predict the efficacy of a monoclonal antibody for severe asthma, and its role as a potential biomarker for type 2 inflammation in allergic diseases has been investigated ever since [ 20 ]. Hoshino et al [ 21 ] reported its utility as a marker of response to sublingual immunotherapy, and Krasilnikova et al [ 22 ] found that the exacerbation of AR was associated with increased periostin levels in nasal secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, it was first reported that the serum periostin level could be utilized to predict the efficacy of a monoclonal antibody for severe asthma, and its role as a potential biomarker for type 2 inflammation in allergic diseases has been investigated ever since [ 20 ]. Hoshino et al [ 21 ] reported its utility as a marker of response to sublingual immunotherapy, and Krasilnikova et al [ 22 ] found that the exacerbation of AR was associated with increased periostin levels in nasal secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Small airways may be the most vulnerable and sensitive to both the rhinobronchial reflex and cytokinemia, which are currently being considered as the main mechanisms of the pathological influence of AR/ARS on the course of BA (17). However, this assumption requires further study, which would include the identification of local and systemic biomarkers of inflammation and remodeling (6,(55)(56)(57). Nevertheless, it is worth noticing that our data are consistent with the results of studies by Iyer and Athavale (34), which showed that patients with AR are characterized by a high risk of latent damage to the small respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…Several cytokines have been involved in Th2-asthma, among them, the alarmins, initiators of T2 inflammation: IL-33, IL-25, and thymic stromal lymphopoietin (TSLP). Alarmins promote the expression of IL-4, IL-5, and IL-13 and increase the levels of periostin [ 8 ].…”
Section: Introductionmentioning
confidence: 99%